Use of artificial intelligence to increase the efficiency of the management accounting system - G.I.; O.V. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
In today’s world, companies are looking for new ways to optimize business processes and reduce costs. The use of artificial intelligence in management accounting allows you to automate routine tasks, analyze large volumes of data and provide valuable information for decision-making. The use of artificial intelligence in management accounting is associated with increasing the efficiency of management accountants, which ensures the effectiveness of the management accounting system as a whole. Artificial intelligence can help avoid errors and reduce the risk of data loss. Knowledge and skills in the use of artificial intelligence are essential for management accounting professionals to remain competitive and effective in the marketplace. Technological innovations, particularly artificial intelligence, will have a significant impact on professional accounting services in the future. The article highlights the skills that specialists need to effectively work with artificial intelligence. The authors also highlight three methods of artificial intelligence that can be effectively used in management accounting: expert systems, data analytics, and neural networks. Expert systems allow management accountants to store and interpret human experience, using it to provide advice and recommendations that facilitate appropriate decision-making based on the evidence provided by expert systems. Data analysis technology allows you to discover new patterns of relationships between data and provide useful conclusions to decision-makers in companies. Neural networks are used to determine the level of compliance with policies in various types of companies and institutions and to detect risky or potentially fraudulent transactions.